Analysis of Teacher's Efforts in Improving Students' Calistung (Read-Write-Arithmetic) Skills During the Transition Period/Analisis Upaya Guru Dalam Meningkatkan Keterampilan Calistung (Baca-Tulis-Aritmatika) Siswa Selama Masa Transisi - Ahyatun Najiah; Yulia Handayani; Makherus Sholeh (Al-Mudarris: Journal Of Education, 2022)
Teachers must provide stimulus to students to be able to achieve optimal learning outcomes. One of them is a stimulus in learning Calistung (reading, writing, and arithmetic) because this Calistung is a milestone for lifelong learning. During the pandemic, learning is carried out online and face-to-face, which is limited because it must be following strict health protocols. Therefore, this study aims to analyze the efforts made by teachers in improving the calistung skills of class IA students at MIN 2 Banjarmasin. The results obtained in this study are the teacher's efforts in improving students' Calistung skills, the teacher plans to learn well through making lesson plans; using learning models, strategies, and methods that enable students to actively participate in learning; holding games that support Calistung learning; provide motivation to increase students' enthusiasm for learning, and provide additional study hours for students who need more guidance in Calistung.